Unusual abundant ions in mass spectra of bifunctional thiols - Iglesias, Luis Emilio (2000)
Mass spectra of omega-merkaptoesters obtained by electron impact ionization at 70 eV showed important ions at m/z 60, 74 and 88. These ions may be useful for diagnosis and could be explained as cyclic sulfur-containg structures. The fact that these ions are neglegible in the spectra of simple primary ions suggests that in the mentioned bifunctional thiols as well as in the parent alpha, omega-hydroxyalkanethiols, the existence of an additional functional group allows the formation of the cyclic ions. Such structures are also proposed to explain some ions observed in mass spectra of 3-mercpato-1,2-propanediol 1-O-acyl derivatives.